2018
DOI: 10.1016/j.palaeo.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal in the Ordovician: Speciation patterns and paleobiogeographic analyses of brachiopods and trilobites

Abstract: The Middle to Late Ordovician was a time of profound biotic diversification, paleoecological change, and major climate shifts. Yet studies examining speciation mechanisms and drivers of dispersal are lacking. In this study, we use Bayesian phylogenetics and maximum likelihood analyses in the R package BioGeoBEARS to reanalyze ten published data matrices of brachiopods and trilobites and produce time-calibrated species-level phylogenetic hypotheses with estimated biogeographic histories. Recovered speciation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 142 publications
3
52
0
Order By: Relevance
“…Lam et al . () conducted a broader biogeographical analysis, using BioGeoBEARS, of multiple brachiopod and trilobite clades in the Peri‐Iapetus region and demonstrated that long‐distance dispersal (dispersal between palaeocontinents) was probably a general biogeographical pattern of most taxa during the Late Ordovician. Biogeographical studies on Ordovician trilobites with similar tropical distributions (Congreve & Lieberman , ; Congreve ) suggested that clades that experienced dispersal events between peri‐Iapetus regions and tropical Gondwana showed increased survivorship and would go on to radiate during the Silurian recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Lam et al . () conducted a broader biogeographical analysis, using BioGeoBEARS, of multiple brachiopod and trilobite clades in the Peri‐Iapetus region and demonstrated that long‐distance dispersal (dispersal between palaeocontinents) was probably a general biogeographical pattern of most taxa during the Late Ordovician. Biogeographical studies on Ordovician trilobites with similar tropical distributions (Congreve & Lieberman , ; Congreve ) suggested that clades that experienced dispersal events between peri‐Iapetus regions and tropical Gondwana showed increased survivorship and would go on to radiate during the Silurian recovery.…”
Section: Discussionmentioning
confidence: 99%
“…A similar increase in ichnodiversity and ecosystem complexity, notably in bioerosion of metazoan reef organisms, has recently been described by Buatois et al (2016). Additional analyses, such as the recently published study by Lam et al (2017), to examine how global-scale changes (in ecosystems or tectonics) influence the local scale process of speciation would be extremely valuable.…”
Section: Speciation During the Gobementioning
confidence: 54%
“…These data link the broader scale patterns directly with the realm of speciation (Lam et al . ). Development of similar species‐level data sets for additional clades and palaeocontinents is necessary to test the generality of this pattern.…”
Section: Speciation During the Gobementioning
confidence: 97%
See 1 more Smart Citation
“…These models rely on combining molecular phylogenies with ancestral state reconstructions to identify the origin of a focal set of taxa and their subsequent dispersal to other regions (Marske et al 2013). Testing how well phylogeographic models including or excluding species' long-distance events explain the current emergent pattern of species cooccurrence within a focal clade can enable understanding the assemblage-level effects of dispersal (Pennington and Dick 2004, Dick et al 2007, Lam et al 2018. More recently, the advent of approximate Bayesian computation (ABC) methods and high-throughput DNA sequencing methods have revolutionized our ability to directly test the effects of different dispersal processes on the aggregate distribution of cooccurring species (Hickerson et al 2010, Chan et al 2014.…”
Section: Phylogeographic Modelsmentioning
confidence: 99%